Long-term recovery following critical illness in an Australian cohort - Kimberley J. Haines; Sue Berney; Stephen Warrillow; Linda Denehy (Journal of Intensive Care, 2018)
Abstract Background Almost all data on 5-year outcomes for critical care survivors come from North America and Europe. The aim of this study was to investigate long-term mortality, physical function, psychological outcomes and health-related quality of life in a mixed intensive care unit cohort in Australia. Methods This longitudinal study evaluated 4- to 5-year outcomes. Physical function (six-minute walk test) and health-related quality of life (Short Form 36 Version 2) were compared to 1-year outcomes and population norms. New psychological data (Center for Epidemiological Studies–Depression, Impact of Events Scale) was collected at follow-up. Results Of the 150 participants, 66 (44%) patients were deceased by follow-up. Fifty-six survivors were included with a mean (SD) age of 64 (14.2). Survivors’ mean (SD) six-minute walk distance increased between 1 and 4 to 5 years (465.8 m (148.9) vs. 507.5 m (118.2)) (mean difference = − 24.5 m, CI − 58.3, 9.2, p = 0.15). Depressive symptoms were low: median (IQR) score of 7.0 (1.0–15.0). The mean level of post-traumatic stress symptoms was low—median (IQR) score of 1.0 (0–11.0)—with only 9 (16%) above the threshold for potentially disordered symptoms. Short-Form 36 Physical and Mental Component Scores did not change between 1 and 4 to 5 years (46.4 (7.9) vs. 46.7 (8.1) and 48.8 (13) vs. 48.8 (11.1)) and were within a standard deviation of normal. Conclusions Outcomes of critical illness are not uniform across nations. Mortality was increased in this cohort; however, survivors achieved a high level of recovery for physical function and health-related quality of life with low psychological morbidity at follow-up. Trial registration The trial was registered with the Australian New Zealand Clinical Trials Registry ACTRN12605000776606.